Safety of Nonlinear Elastic and Elastic Plastic Rod Systems Provided By Static, Energy and Dynamic Methods - Khamrabaeva Nilufarkhan Azizovna ,; Muslimova Pokizakhan Shukhratovna, (European Journal of Life Safety and Stability (2660-9630), 2022)
the article is devoted to identifying the main patterns of behavior of models of nonlinear elastic and elastic-plastic spatial rod systems in solving the problem of stability, reliability and dynamics. From various options for numerical analysis of studies of certain theoretical positions, one can choose the simplest ones. When using this method of calculation, familiar to engineers for most of the tasks, there is no need for direct application, which in engineering practice in a significant study of the stability of spatial rod systems.